International Folk Medicine. - Abdurashitova Sharafat Abdumajitovna; Muyassarova Mukhabbat Muhammadievna; Z.A.Abdumannonova; G.A.Kenjayeva (Zien Journals, 2024)
In this article, the role of international folk medicine and the analysis of research conducted in this field, as well as the results of practical work, methods of folk medicine that have been proven to be effective and safe, and the need to harmonize traditional medicine with modern medicine were highlighted
Keywords: Traditional medicine; health promotion; health care; modern medicine